One byte at a time: gathering best practices, guidelines, and resources for data standards to support ocean exploration and characterization - Cantwell, Kasey; Demopoulos, Amanda W. J.; Hebner, Mitchell G.; Medley, Rachel; Mueller, Mark; Netburn, Amanda N. (Frontiers in Marine Science, 2023)
Initiated through Presidential direction and now codified, the National Ocean Mapping, Exploration, and Characterization (NOMEC) Council comprises leaders from U.S. federal agencies with a shared goal of mapping all waters of the United States and exploring and characterizing priority areas. The NOMEC Council’s two Interagency Working Groups, Ocean and Coastal Mapping (IWG-OCM) and Ocean Exploration and Characterization (IWG-OEC), both achieved major milestones recently with the 2023 release of the Draft Standard Ocean Mapping Protocols (SOMP) and the 2022 publication of the National Priorities for Ocean Exploration and Characterization. Building on this groundwork, the IWG-OEC is now looking to define and share best practices, guidelines, and resources for ocean exploration and characterization with the long-term goal of increasing community wide standardization to help achieve consistent common practices. First, the IWG-OEC plans to compile federal agency resources and share them in a newly developed online resource repository. The next phase is for the IWG-OEC to create opportunities for non-federal sectors to provide input on developing and populating this repository with additional content (existing standards and protocols, best practice and guidelines documents, etc.). After experts representing multiple sectors are identified, a series of results-oriented workshops are planned to provide input on all aspects of the data, products, and services from exploration and characterization. Finally, the IWG-OEC plans to widely share the online repository of best practices and standard operating procedures. A systematic, transparent, and collaborative process to share standards and protocols can help to enhance the interoperability of data and inform new lines of inquiry, discovery, research, and innovation.